CMV-specific immune reconstitution following allogeneic stem cell transplantation. Issue 8 (16th November 2016) - Blyth, Emily; Withers, Barbara; Clancy, Leighton; Gottlieb, David
ABSTRACT: Cytomegalovirus (CMV) remains a major contributor to morbidity and mortality following allogeneic haemopoietic stem cell transplant (HSCT) despite widespread use of viraemia monitoring and pre-emptive antiviral therapy. Uncontrolled viral replication occurs primarily in the first 100 d post transplant but this high risk period can extend to many months if immune recovery is delayed. The re-establishment of a functional population of cellular effectors is essential for control of virus replication and depends on recipient and donor serostatus, the stem cell source, degree of HLA matching and post-transplant factors such as CMV antigen exposure, presence of GVHD and ongoing use of immune suppression. A number of immune monitoring assays exist but have not yet become widely accessible for routine clinical use. Vaccination, adoptive transfer of CMV specific T cells and a number of graft engineering processes are being evaluated to enhance of CMV specific immune recovery post HSCT.